MENINGKATKAN KEMAMPUAN GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL (KKM) DI SD NEGERI 018 RAMBAH MELALUI KELOMPOK KERJA GURU SEKOLAH (KKGS) - Mesrawati Mesrawati (JURNAL PENDIDIKAN ROKANIA, 2016)
Based on the analysis showed that the increased ability of teachers to assign a minimum completeness criteria from the first cycle to the second cycle. Achievement Kelompok Kerja Guru Sekolah activities contained in the action II. Therefore it can be concluded that through Kelompok Kerja Guru Sekolah can enhance the ability of teachers set minimum completeness criteria in SD Negeri 018 Rambah. Thus it can be recommended to teachers and other researchers that the activities of the Working Group Master can be used as an alternative to improve the ability of teachers set Kriteria Ketuntasan Minimal (KKM)